Pelaksanaan Bimbingan Belajar sebagai Upaya Mengatasi Kesulitan Belajar Matematika Siswa dari Keluarga yang Memiliki Keterbatasan Waktu Bimbingan di Rumah - Agusna, Rasi; Lukman Ibrahim; Syifa Fadilla (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This research aims to describe the implementation of tutoring as an effort to overcome the difficulties in learning of student of MTsN 2 Banda Aceh and MTsN 4 Banda Aceh with family that have limited time to guide children at home. It uses the method of case study of qualitative approach. Data were collected by interviewed and observational techniques and analyze by thematic techniques. Two students, one teacher and two parents of each school were interviewed. One class from each school also observed during the tutorials. The results show that the implementation of tutoring received a positive response from students by showing their enthesiastic in learning and solving problems. As the impact, they became be better able in solving mathematics problem and describe mathematical concepts without so depending from others. Mathematics teacher and parents also gave positive response for the tutorial. The implementation of the tutorial is effectively be one of the efforts to overcome learning difficulties for students who come from families with their parents have limited time to guide learning at home.